Understanding cancer information-scanning behavior on WeChat among young Chinese adults: applying a modified comprehensive model of information seeking - Ma, QianYing; Tham, Jen-Sern; Bidin, Rosmiza; Syed Zainudin, Sharifah Sofiah (SAGE Publications, 2025)
Objective: Given the increasing incidence of cancer among younger populations and the prominent role of WeChat in health information acquisition, young Chinese adults are more likely to encounter and engage with cancer-related information on WeChat. However, limited empirical research has examined the motivations behind young adults’-cancer information-scanning behavior (CISB) on this platform. This study aims to address this gap by applying the Comprehensive Model of Information Seeking (CMIS) to identify the key predictors of CISB among young Chinese adults. Methods: An online cross-sectional survey was conducted on WeChat from October 14 to October 24, 2023, targeting young Chinese adults ages 18–44. Using convenience and snowball sampling methods, a total of 1484 valid responses were collected. Results: Structural equation modeling (SEM) indicated that perceived susceptibility, WeChat self-efficacy, and perceived credibility directly predicted perceived utility, whereas perceived severity did not. Additionally, both perceived credibility and perceived utility significantly predicted CISB on WeChat. Mediation analysis employing PROCESS Macro revealed that perceived utility mediated the relationships between health-related factors (i.e., perceived susceptibility, severity, and WeChat self-efficacy) and CISB on WeChat. Conclusions: The findings highlight the mediating and enhancing role of perceived utility and extend CMIS applicability in the context of CISB on WeChat. These findings provide practical implications for policymakers and health professionals to create more effective cancer communication strategies.